Farklı malzemelerin radyografik yöntemle yarı-değer kalınlığının tespiti - Üçer, Kemal (Enerji Enstitüsü, 1997)
Bu çalışmada, tahribatsız muayene metodlarından radyografik yöntem kullanılarak farklı yoğunluktaki malzemelerin yan-değer kalınlıklarının deneysel olarak tespitine çalışılmıştır. Deneysel çalışmalar sırasında yapılan tüm radyografik incelemeler, Nükleer Uygulamalar Anabilim Dalı'nda bulunan 4 mm odak boyutlu Balteau GR 300 X-ışım ve 4 mm odak boyutlu Kobalt-60 (Co-60 ) kaynaklı gama ışını cihazları ile gerçekleştirilmiştir. Yoğunlukları bilinen veya denel olarak bulunan malzemeler, deneylerin gerçekleştirileceği gama ışını ve değişik kilovoltajlardaki X-ışınlan ile radyografik çekim şartlarına uygun halde tasarlanmıştır. Tasarlanan bu örnekler, basamaklı penetremetreler haline getirilmiş, daha sonra X ve gama ışınlan kullanılarak deneyler gerçekleştirilmiştir. Tüm bu deneyler sonucu elde edilen radyograflardaki basamakların densitometre ile ölçülen yoğunluk farklılıkları incelenmiştir. Bu film yoğunluk farkları ile malzeme kalınlıkları arasındaki ilişkiden hareketle, değişik kilovoltajlardaki X ve gama ışınlan için denel olarak yan-değer kalınlıkları tespit edilmiştir.

in this study, radiographic techniques have been used by measuring the Half- Value Layer Ticknesses of difFerent materials. Ali radiographical applications implemented during this experimental study have been realized by using Balteau GR-300 X-ray machine and a gamma ray instrument with Cobalt-60 ( Co- 60 ) source in Nuclear Appliction Division. The concept of the quality control has been developed in parallel with modern technology. An industrial product must be qualified in a good place in the market. For this reason, the quality control tests must be applied and the limits of acceptance and rejection criteria must also be determined. Nondestructive testing methods, especially radiographic test are vvidely used in the production and process control, besides the research- development studies. Radiography today is öne of the most important, most versatile, offall nondestructive test methods used in modern industry. industrial radiography continues to play an important role many industries by helping to assure the product qualitiy and to conduct research for better materials and process. Nevertheless, there are some of the advantages and limitations of radiographic testing as a quality assurance procedure are as follovvs : l - ADVANTAGES A - Can be used most materials B - Provides a parmanent visiual image record of the test specimen C - Reveals the internal nature of the film D - Discloses fabrication errors and often indicates necessary corrective action ( separating acceptable and unacceptable material in accordance vvith predetermined standarts) E - Reveals structural discotiniuties, assembly errors and mechanicaly failures
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Radyografi; Tahribatsız muayene yöntemleri; Radiography; Nondestructive inspection methods